I "get" you, babe: Reflective functioning in partners transitioning to parenthood. (June 2020) - Borelli, Jessica L.; Slade, Arietta; Pettit, Corey; Shai, Dana
Reflective functioning (RF) is a construct that has gained tremendous traction in the developmental psychology literature, demonstrating robust associations with parent–child attachment and interactional quality. Although theorists argue that RF should have meaningful links with relationship quality across the life span, to date this construct has not been applied to the study of adult romantic partnerships. The goal of the present investigation is to introduce the construct of Partner RF, the capacity to reflect on the thoughts and feelings of one's partner and to consider their roles in guiding behavior in one's partner and oneself. Next, we explore the degree to which Partner RF is associated with a range of theoretically related constructs—one's partner's Partner RF, as well as one's own parental RF, attachment, relationship satisfaction, and coparenting—in first-time parents. In a longitudinal study of N = 107 primiparous couples, we found positive associations between mothers' and fathers' Partner RF and between mother's Partner RF and their parental RF. Partner RF is higher among women who report lower prenatal attachment avoidance and demonstrate more prenatal positive communication with their partners. Counterintuitively, higher levels of maternal Partner RF predict greater decreases in couple and coparenting satisfaction across the transition to parenthood. Partner RF may be an important construct to measure and understand in terms of its role in couple relationship functioning and parental well-being.